Sistem Informasi Bahasa Rejang Berbasis Natural Language Processing (NLP) Untuk Pelestarian Budaya Lokal - Wibowo, Sastya Hendri; Diana, Diana (Journal of Information System Research (JOSH), 2024)
Regional languages in Indonesia have their own differences both in terms of morphology and dialect, such as the Minang language in West Sumatra, the Batak language in North Sumatra, the Sundanese language in West Java and also the Rejang language in Bengkulu. Each province is certain to have its regional language dictionary in the form of a printed book, but not necessarily a digital dictionary. In the current era of computer technology, it is very important to build a language translation application. So that it can make it easier for the community, especially the Indonesian people, to communicate between one person and another with a different regional language. Therefore, building a digital dictionary is the main requirement as a source of supporting data used by language translation applications. In Bengkulu, there is currently no digital dictionary for Rejang, nor is there an application for translating Rejang to Indonesian or vice versa. Meanwhile, to build a language translator application, a left corner parsing algorithm is needed. The left corner parsing algorithm is a combination of two algorithms, namely the top down parsing algorithm and the bottom up parsing algorithm. This algorithm's task is to check each word in a sentence, then match a grammar pattern to the results of the inspection. This inspection process will become a word checker. Rejang language is a regional language used by approximately 500,000 native speakers who live in Rejang Lebong Regency and the surrounding areas in Bengkulu Province and South Sumatra Province. Basically, the Rejang language belongs to the Malay or Indonesian language family. The Rejang language not only has a structured morphology but also a script, namely the Kaganga script. Until now there has been no research examining the Rejang language regarding the Rejang language information system based on natural language processing (NLP) in Bengkulu province for the preservation of local culture. The result of this research is a Rejang language information system application that displays information about digital dictionaries, translators and Rejang cultural information that is useful for the people of Bengkulu Province.